Study of Elderly Needs to Service of Santun Lansia Health Center - Kurniawan Yudianto; Fadiah Izzati Salim; Citra Windani Mambang Sari (Universitas Padjadjaran, 2018)
When a person become elderly people will slowly decline in physical function and psychological aspect affecting the economic and social conditions. The purpose of this study is to identify the needs of the elderly to Age-friendly Community Health Center (Puskesmas Santun Lansia) services in Puskesmas Puter. This research using quantitative descriptive method with 96 respondents who were taken by purposive sampling technique. The data collection technique using a questionnaire based on the concept of Age-friendly Community Health Center. Results were analyzed using univariate analysis with mean/median.The result showed that 86.5% of elderly people requiring Age-friendly Community Health Centerservices and 47% of elderly people consider it important. All of respondent require servicing at dimensions promotive, preventive, rehabilitative, and ease of service. While the dimensions of curative required by all respondents. Most elderly people consider it important dimension of service on promotive, preventive, curative, rehabilitative, and ease of service.Based on research, it is expected the collaboration between the City Health Department and Community Health Center in the development of special program for elderly to improve quality of care for the elderly.